PENGEMBANGAN LKPD PEMBELAJARAN BERBANTUAN GAMIFIKASIPADA PEMBELAJARAN CERPEN KELAS XI SMK MADANI MARINDAL I - Pasaribu, Ummi Salamah; Andriany, Liesna; Ali, Ali (Program Studi Pendidikan Biologi, 2025)
This study aimed to investigate the development and feasibility of procedure text teaching materials based on e-handouts with a local culture approach in enhancing the Higher Order Thinking Skills (HOTS) of class XI at SMK Madani Marindal 1. It used a Research and Development (RD) method using the ADDIE model, that consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The population and sample of this study include 44 students from three different classes: Office Administration (OTKP), Automotive Engineering (TBSM), and Computer and Network Engineering (TKJ). The results indicated the developed teaching material is deemed feasible. The first content expert rated as “Feasible” or 80%, while the second content expert obtained “Feasible” or 82%. The first design expert rated as “Highly Feasible” or 91%, and the second design expert rated as “Feasible” or 80%. The teacher’s assessment obtained “Highly Feasible” or 87%. The field implementation test involving 44 students across the three classes (21 TKJ, 15 TBSM, and 8 OTKP students) obtained “Feasible” or 76%. Additional data were collected through interviews with teachers and students